Lung adenocarcinoma and splenic histiocytic sarcoma in an African pygmy hedgehog (Atelerix albiventris) - Zanoti, Isabela Coelho; Gouveia, Bethânia Almeida; Santos, Alessandra Loureiro Morales dos; Ramos, Fernanda Ramalho; Momo, Claudia (Brazilian Journal of Veterinary Pathology, 2023)
The African pygmy hedgehog is increasingly being kept as a pet, and studies regarding the primary diseases that affect this species are essential for advancing medicine in these animals. This report aims to describe a case of an adult male hedgehog living in captivity. The hedgehog presented progressive weight loss and lethargy. An abdominal ultrasound examination was performed, revealing a splenic mass. Therefore, symptomatic treatment was chosen. After three months, with no clinical improvement, the animal was euthanized. The cadaver underwent necropsy, and histopathological evaluation with Hematoxylin and Eosin staining revealed two distinct neoplasms in different organs: pulmonary adenocarcinoma and round cell neoplasm in the spleen. Additionally, non-neoplastic lesions were observed in other organs. The splenic tissue was subjected to an immunohistochemical diagnostic panel using IBA1, CD3, PAX5, MUM1, and AE1AE3 markers. Positive staining for IBA1 was observed, favoring the diagnosis of histiocytic sarcoma. We emphasize the importance of preventive veterinary medicine in assessing these animals’ health status and detecting possible neoplastic processes. Tumors are commonly described in this species, and clinical signs usually are nonspecific, leading to the animal’s death or euthanasia.